Impact of anticoagulants in elderly patients who suffer a hip fracture. Should we have a different approach? - Lotti, Francisco; Elizondo, Cristina Maria; Barla, Jorge; Carabelli, Guido; Soruco, Maria Lilliana; Boietti, Bruno Rafael; Benchimol, Javier Alberto (Acta Biomedica Atenei Parmensis, 2020)
Introduction: Hip fracture in the elderly is a frequent problem. Chronic treatment with anticoagulants is common in these patients, and may delay surgery. Objectives: To compare time to surgery, hospital stay, in-hospital and 90 days complications between anticoagulated (A) and non-anticoagulated (NA) groups. Methods: Retrospective cohort of >64 years-old patients with acute hip fracture. Period June-2014 to December 2019. We estimated crude and adjusted OR (95%CI) for in-hospital complications with logistic regression model. We report the crude and adjusted HR for readmission and 90-day mortality with Cox proportional hazards model. Results: Of the 1058 patients, 123 (11%) were anticoagulated. Time to surgery was 26.4 hours (IIQ 13.9-48) in A and 24 hours (IIQ 2.3-48) in NA, p0.001. Hospital stay was 7 days (IIQ 5-9) in A and 6 days (IIQ 5-10.5) NA, p0,000. In-hospital complications were 17 (14%) in A and 81 (9%) in NA, p0.064. The adjusted OR was 1.53 (95%CI 0.8-2.7) p0.138. For 90-day readmission, the crude HR was 1.51 (95%CI 0.99-2.29) p0.053 and the adjusted HR was 1.31 (95%CI 0.85-2.00) p0,09. For 90-day mortality, the crude HR was 0.80 (95%CI 0.45-1.43) p0.464 and the adjusted HR was 0.70 (95% CI 0.39-1.25) p0.239. Discussion: While we found differences between groups in time to surgery and hospital statistics, their clinical relevance should be reviewed.